2002
DOI: 10.4039/ent134447-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the Pissodes strobi complex (Coleoptera: Curculionidae)

Abstract: Morphometric data were collected on 15 characters in adults of the species of the Pissodes strobi complex (P: nemorensis (Germar), P: schwarzi Hopkins, P: strobi (Peck), and P: terminalis Hopping). Data were examined using stepwise discriminant analysis to determine if all characters contribute significantly to the diagnosis of taxa, and their relative amounts of resolving power were illuminated using canonical variates analysis. Discriminant functions were generated to diagnose species. Separate discriminant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Sixty-eight female and 72 male Pissodes specimens collected from nine sites across South Africa (Online Resource 1) were characterised by measuring 15 morphometric characters (Online Resource 5) used to discern members within the P. strobi complex (Williams & Langor, 2002). The specimens were measured using calibrated AxioCam ICc 5 Zeiss camera attached to a Carl Zeiss Stemi 2000 stereo microscope.…”
Section: Morphometric Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixty-eight female and 72 male Pissodes specimens collected from nine sites across South Africa (Online Resource 1) were characterised by measuring 15 morphometric characters (Online Resource 5) used to discern members within the P. strobi complex (Williams & Langor, 2002). The specimens were measured using calibrated AxioCam ICc 5 Zeiss camera attached to a Carl Zeiss Stemi 2000 stereo microscope.…”
Section: Morphometric Measurementsmentioning
confidence: 99%
“…Morphometric data measured in the present study and those reported by Williams and Langor (2002) were compared by factor analysis (FA) in order to describe morphometric similarity/difference of the South…”
Section: Morphometric Data Analysismentioning
confidence: 99%
See 3 more Smart Citations